1998
DOI: 10.1038/sj.gt.3300608
|View full text |Cite
|
Sign up to set email alerts
|

The levels of integrin αvβ5 may predict the susceptibility to adenovirus-mediated gene transfer in human lung cancer cells

Abstract: Adenovirus-mediated transfer of growth-inhibiting moldependent on the infection efficiency. Growth inhibition ecules, such as p53, shows promise as an effective was induced in all cell lines tested following infection with method of suppressing the growth of cancer cells. As the an adenovirus containing p53, regardless of the genetic basis for in vivo studies, we examined transfection status of their endogenous p53 provided a sufficient efficiency using 15 human lung cancer cell lines that differ amount of p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 18 publications
2
27
1
Order By: Relevance
“…We have previously shown that H157 cells, which have a mutated p53 gene, undergo apoptosis when infected with Ad5p53. 23 Ad5p53 infection of H157 cells at MOI 0.1 showed a weak cytotoxic effect compared with Ad5VEGFE1. Similar results were obtained with A427 cells (data not shown).…”
Section: Specific Cell Killing Efficacy Of Vegf Promoter Driving Cradmentioning
confidence: 88%
See 1 more Smart Citation
“…We have previously shown that H157 cells, which have a mutated p53 gene, undergo apoptosis when infected with Ad5p53. 23 Ad5p53 infection of H157 cells at MOI 0.1 showed a weak cytotoxic effect compared with Ad5VEGFE1. Similar results were obtained with A427 cells (data not shown).…”
Section: Specific Cell Killing Efficacy Of Vegf Promoter Driving Cradmentioning
confidence: 88%
“…We also used wild-type Ad5 (Ad5wt) as a control. 23 The viruses were propagated in the Ad packaging cell line, 293HEK, and purified by double cesium chloride density gradient centrifugation, followed by dialysis against phosphate-buffered saline with 10% glycerol. The viral particle (VP) concentration was determined spectrophotometrically, using a conversion factor of 1.1 Â 10 12 VPs per absorbance unit at 260 nm, 24 and standard plaque assays on 293 cells were performed to determine infectious particles.…”
Section: Adenovirus Vectorsmentioning
confidence: 99%
“…This variability could be at least partially attributed to the variability in CAR and integrin expression levels that are required for viral uptake into the cells. [76][77][78][79][80][81][82][83][84] To demonstrate suppression of cell growth in the sarcoma cell lines, lower doses of Ad-wtp53 were used so as not to produce an overt cytotoxic effect with massive cell death as seen in our previous experiments. Doses ranging from 0.1 to 0.4 PFU/cell (2-10 PFU/cell for RD) were used and a cell count was performed every 24 hours for 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 gene of NCI-H157 is mutated (exon 8, codon 298, CAG to TAG) 4 and that of NCI-H1299 is deleted, and both cell lines exhibited a high gene transfer effect when cultured with adenoviral vectors. 5 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) was purchased from Sigma (St Louis, Mo). The anticancer agents used included CDDP, carboplatin (CBDCA), and paclitaxel (all from Bristol-Myers Squibb, Tokyo, Japan); 7-ethyl-10-hydroxy-camptothecin (SN-38) (from Yakult Honsha, Tokyo, Japan); bleomycin (BLM) and VP-16 (from Nippon Kayaku, Tokyo, Japan); 5-FU and adriamycin (ADR) (from Kyowa Hakko Kogyo, Tokyo, Japan); cyclophosphamide (CPM), vindesin (VDS), and ifosfamide (IFO) (from Shionogi and Co., Osaka, Japan); and SM-5887-13-OH (an active metabolite of newly developed anthracyclin) (from Sumitomo Pharmaceuticals, Osaka, Japan).…”
Section: Cell Culture and Chemicalsmentioning
confidence: 99%
“…Replication-defective E1 and E3 adenoviral vectors expressing human wt p53 5,6 were prepared as described previously. 7 A cDNA coding for human wt p53 (kindly provided by Dr. Vogelstein, Program in Human Genetics, Johns Hopkins Oncology Center, Baltimore, Md) was placed into a cassette cosmid vector, pAdexCA1w (provided by Dr. Saito, University of Tokyo, Tokyo, Japan), under a CA promoter comprising a cytomegalovirus enhancer and chicken ␤-actin promoter (pAdex1w/p53).…”
Section: Adenoviral Vectormentioning
confidence: 99%